2022
DOI: 10.1590/fm.2022.35148
|View full text |Cite
|
Sign up to set email alerts
|

Sex and age differences in sensory threshold for transcutaneous electrical stimulation

Abstract: Introduction Pain is one of the main symptoms prevalent in most pathologies. Transcutaneous Electrical Nerve Stimulation (TENS) represents not only a therapeutic measure, but also a mean to quantify the neurosensory and pain perception in patients with chronic pain. Objective To evaluate the relationship between sex and age with neurosensory thresholds (sensory threshold and tolerance threshold) in the application of therapeutic current in patients with chronic pain. Methods Forty-five patients with chron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
(6 reference statements)
0
0
0
Order By: Relevance
“…The mean differences between male and female subjects were 0.18, 0.22, 0.44, 0.88, and 0.61 mA at five different measurement points [8]. A study by Saraiva et al [23] also found a lower sensory threshold in women compared to men-13.77 vs. 19.57 mA. The authors pointed out the anatomical and physiological discrepancies that can generate differences in sensory response, including size of the neuromotor course and amounts of neurotransmitters [23].…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The mean differences between male and female subjects were 0.18, 0.22, 0.44, 0.88, and 0.61 mA at five different measurement points [8]. A study by Saraiva et al [23] also found a lower sensory threshold in women compared to men-13.77 vs. 19.57 mA. The authors pointed out the anatomical and physiological discrepancies that can generate differences in sensory response, including size of the neuromotor course and amounts of neurotransmitters [23].…”
Section: Discussionmentioning
confidence: 79%
“…A study by Saraiva et al [23] also found a lower sensory threshold in women compared to men-13.77 vs. 19.57 mA. The authors pointed out the anatomical and physiological discrepancies that can generate differences in sensory response, including size of the neuromotor course and amounts of neurotransmitters [23]. A study by Guirro et al [24] showed that even using two different current frequencies, i.e., 5 and 50 Hz, the threshold of sensory perception in women was lower than that in young and elderly men.…”
Section: Discussionmentioning
confidence: 99%